Ocean Acidification and Warming Lead to Increased Growth and Altered Chloroplast Morphology in the Thermo-Tolerant Alga Symbiochlorum hainanensis - Gong, Sanqiang; Jin, Xuejie; Xiao, Yilin; Li, Zhiyong (Frontiers in Plant Science, 2020)
Ocean acidification and warming affect the growth and predominance of algae. However, the effects of ocean acidification and warming on the growth and gene transcription of thermo-tolerant algae are poorly understood. Here, we determined the effects of elevated temperature (H) and acidification (A) on a recently discovered coral associated thermo-tolerant alga Symbiochlorum hainanensis by culturing it under two temperatures (26.0 °C and 32.0 °C) crossed with two pH levels (8.16 and 7.81). The results showed the growth of S. hainanensis was positively affected by H, A and the combined treatment (AH). However, the no superimposition effect of H and A on the growth of S. hainanensis was observed under the AH. The analysis of chlorophyll fluorescence, pigment content and subcellular morphology indicated the chloroplast morphogenesis (enlargement) along with the increase of chlorophyll fluorescence and pigment content of S. hainanensis might be a universal mechanism for promoting growth of S. hainanensis. Transcriptomic profiles revealed the effect of elevated temperature on the response of S. hainanensis to acidification involved in down-regulation of photosynthesis and carbohydrate metabolism related genes but up-regulation of genes related to antioxidant and ubiquitination processes. Overall, this study firstly reports the growth, morphology and molecular response of the thermo-tolerant alga S. hainanensis to future climate changes, suggesting the predominance of S. hainanensis in its associated corals and/or coral reefs in the future.